Prognostic models for identifying adults with intellectual disabilities and mealtime support needs who are at greatest risk of respiratory infection and emergency hospitalisation. Issue 8 (11th May 2017) - Perez, C. M.; Wagner, A. P.; Ball, S. L.; White, S. R.; Clare, I. C. H.; Holland, A. J.; Redley, M.
Abstract: Background: Among adults with intellectual disabilities (ID), problems with eating, drinking and swallowing (EDS), and an associated need for mealtime support, are common, with an estimated 15% of adults known to specialist ID services requiring mealtime support. We set out to identify which adults with ID who receive mealtime support are at an increased risk of respiratory infections and emergency hospitalisation related to EDS problems . Method: An exploratory, prospective cohort study was undertaken in the East of England. At baseline, structured interviews with the caregivers of 142 adults with ID and any type of mealtime support needs were used to gather information on health and support needs over the previous 12 months. These interviews were repeated at follow‐up, 12 months later. The resulting dataset, covering a 24‐month period, was analysed with logistic regression, using model averaging to perform sensitivity analysis, and backwards step‐wise variable selection to identify the most important predictors. Results: Individuals with a history of respiratory infections (in the first year of study), those who had epilepsy and those with caregiver‐reported difficulty swallowing were most likely to have respiratory infections in the second year. Adults with increasing mealtime support needs, epilepsy and/or full mealtime support needs (fed mainly or entirely by a caregiver or enterally) were at increased risk of emergency hospitalisation for EDS‐related problems . Conclusions: Our findings highlight the importance of carefully monitoring health issues experienced by adults with ID and EDS problems, as well as their eating, drinking and swallowing skills. However, the models developed in this exploratory research require validation through future studies addressing the EDS problems commonly experienced by adults with ID and their implications for health outcomes and quality of life. Further research into the relationship between epilepsy and EDS problems would provide much‐needed insight into the complex relationship between the two areas.